Pressure Transient Analysis using Generated Simulation Reservoir Data for Dual Porosity Model of Naturally Fractured Reservoir - Taufan Marhaendrajana; Doddy Abdassah; Sri Feni Maulindani (Journal of Earth Energy Engineering, 2023)
A naturally fractured reservoir today plays a significant role in improved worldwide oil and gas production. More than half of the resource is mostly found in this reservoir. In this reservoir, there are two porous media: the matrix, which acts as the fluid source in this reservoir, and the fractures, which act as the fluid network that flows to the wellbore. Many authors have researched works to model this reservoir. There are two models are done in this study, such as Warren and Root model, where the fluid flow mechanism matrix to fractures is known as pseudosteady-state flow and the Kazemi-Gilman model is known as transient interporosity flow. Reservoir engineers generally utilize pressure transient analysis to determine this reservoir's characteristics. The purpose of this study is to assess whether it is feasible to verify the parameters of the reservoir for pressure transient analysis using a synthesis simulation model. It also aims to observe how reservoir parameters behave in relation to the characteristics of naturally fractured reservoirs by utilizing various values for porosity, permeability, and fracture spacing.